Nitrogen Response and Economics for Irrigated Corn in Nebraska - Dobermann, A.; Wortmann, C.S.; Ferguson, R.B.; Hergert, G.W.; Shapiro, C.A.; Tarkalson, D.D.; Walters, D.T. (Wiley, 2011)
Nitrogen management recommendations may change as yield levels and efficiency of crop production increase. The mean yield with nutrients applied in 32 irrigated corn (Zea mays L.) trials conducted across Nebraska from 2002 to 2004 to evaluate crop response to split‐applied N was 14.8 Mg ha−1 The mean economically optimal nitrogen rates (EONR) for irrigated corn varied with the fertilizer N/grain price ratio. At a fertilizer N/corn price ratio of 7 the EONR was 171, 122, and 93 kg ha−1, respectively, for cropping systems with corn following corn (CC), soybean [Glycine max (L.) Merr.] (CS), and drybean (Phaseolus vulgaris L.) (CD). At this price ratio the present University of Nebraska (UNL) recommendation procedure gave mean N recommendations that were 17.2 and 68.1 kg ha−1 higher than the mean EONR determined in this study for CC and CD, respectively, but essentially equal to mean EONR for CS. The UNL algorithm, adjusted for mean cropping system EONR gave more accurate prediction of site‐year EONR than alternative N rate predictions for CC and CD with returns to applied nitrogen (RTN) of –$22 and –$13 ha−1 compared with measured site‐year EONR. Prediction of site‐year EONR using mean EONR adjusted for soil organic matter was more accurate for CS than other methods with an RTN of –$6 ha−1 compared with measured site‐year EONR. Further research is needed to extend the results to: lower yield situations, alternatives to split application of N, and adjustment of EONR to protect against inadequate N in atypical seasons or for environmental protection.